2011
DOI: 10.1515/cclm.2011.608
|View full text |Cite
|
Sign up to set email alerts
|

Serum APRIL, a potential tumor marker in pancreatic cancer

Abstract: Our results indicate that serum APRIL, as a potential biomarker, has a positive diagnosis and prognosis value for pancreatic cancer. Moreover, the combination assay of APRIL and CA19-9 is highly sensitive to pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
0
21
1
Order By: Relevance
“…In the present study, we found that levels of the serum marker of acute inflammation (CRP) and an inflammatory mediator (TNFSF13) were significantly higher in patients with PDAC-DM than in those without diabetes and in pancreatitis patients. Though the serum levels of CRP and TNFSF13 in patients with PDAC-DM were not directly compared with those of healthy individuals in our study, the serum CRP and TNFSF13 levels in patients with chronic pancreatitis were shown to be slightly higher and the same as those of healthy individuals, respectively [18][19][20]. Our data demonstrated similar levels of CRP mRNA expression in tissues from patients with and without PDAC-DM, and in patients with chronic pancreatitis, excluding the possibility that PDAC lesions are the source of the elevated CRP in the serum of patients with PDAC-DM.…”
Section: Discussioncontrasting
confidence: 61%
“…In the present study, we found that levels of the serum marker of acute inflammation (CRP) and an inflammatory mediator (TNFSF13) were significantly higher in patients with PDAC-DM than in those without diabetes and in pancreatitis patients. Though the serum levels of CRP and TNFSF13 in patients with PDAC-DM were not directly compared with those of healthy individuals in our study, the serum CRP and TNFSF13 levels in patients with chronic pancreatitis were shown to be slightly higher and the same as those of healthy individuals, respectively [18][19][20]. Our data demonstrated similar levels of CRP mRNA expression in tissues from patients with and without PDAC-DM, and in patients with chronic pancreatitis, excluding the possibility that PDAC lesions are the source of the elevated CRP in the serum of patients with PDAC-DM.…”
Section: Discussioncontrasting
confidence: 61%
“…Although APRIL has low or no expression in various normal cells, previous studies have shown that it is overexpressed in many malignancies, such as colorectal cancer [13], pancreatic cancer [26], and gastric cancer [27], suggesting that APRIL plays an important role in the carcinogenesis of these tumors. Moreover, APRIL also owns an ability to stimulate tumor cell proliferation and survival in vitro and in vivo by interaction with the intracellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…This marker, representing A Proliferation Inducing Ligand (APRIL) is a member of the Tumor Necrosis Factor (TNF) super family. It essentially is over expressed [12] in pancreatic cancer but only weakly if not at all in the normal pancreatic glandular tissue. The marker was found to be increased in patients with pancreatic cancer which proved to show positive correlation with CEA and CA19.9 levels in the serum The sensitivity of April alone in diagnosing the presence of malignancy was 70.1% when compared with that of CEA alone (56.7%) and similarly somewhat better than CA 19.9 alone.…”
Section: Origin Of the Diagnostic/therapeutic Tumor Markers Expressedmentioning
confidence: 97%
“…The marker was found to be increased in patients with pancreatic cancer which proved to show positive correlation with CEA and CA19.9 levels in the serum The sensitivity of April alone in diagnosing the presence of malignancy was 70.1% when compared with that of CEA alone (56.7%) and similarly somewhat better than CA 19.9 alone. The sensitivity increased when APRIL was used in combination with CA19.9 reaching a level of 88.1% [12].…”
Section: Origin Of the Diagnostic/therapeutic Tumor Markers Expressedmentioning
confidence: 99%